Pengaruh pemberian ekstrak daun Alfalfa (Medicago sativa) terhadap profil lipid dan kadar malondialdehida tikus hiperkolesterolemia - Joyeti Darni; Kusmiyati Tjahjono; Muchlis Achsan Udji Sofro (Jurnal Gizi Klinik Indonesia, 2016)
Background: Hypercholesterolemic as an indicator of cardiovascular disease is a major cause of morbidity and mortality in the world. Increased oxidative stress in hypercholesterolemic triggers lipid peroxidation effect directly on the cell membrane damage and initiate various diseases. The use of natural materials with relatively few side effects is an hypercholesterolemic management alternative. Experimental studies showed that Alfalfa leaf extract had an effective antioxidant activity.Objective: To determine the effect of Alfalfa leaf extract on serum lipids and malondialdehyde (MDA) level of hypercholesterolemic rats.Method: Pre-posttest randomized control group used twenty-eight male Sprague-Dawley rats were randomly divided into four groups, hypercholesterolemic without treatment (control), hypercholesterolemic with extract at dose 20 mg/200 g/d (X1), dose 40 mg/200 g/d (X2), dose 60 mg/200 g/d (X3) for 21 days after the rats got hypercholesterolemic. Serum lipid was measured by CHOD-PAP method and level of MDA plasma was measured by TBARS method. A hypothesis test was analyzed by One Way ANOVA continued by Post hoc LSD test.Results: Alfalfa extract significant decrease in serum total cholesterol (114.18±3.0 mg/dl; p<0.001). LDL cholesterol level was the lowest in group X3 (45.26±6.03 mg/dL; p<0.001), and triglycerides level was the lowest in group X3 (77.33±2.69 mg/dL; p<0.001). There were no differences in MDA plasma level was the lowest in the group X3 (2.07±0.09 nmol/ml; p<0.001) and a significant increase in serum HDL cholesterol (43.21±7.80 mg/dL; p<0.001).Conclusion: The treatment of Alfalfa (Medicago sativa) leaf extract gives an effect of lower total cholesterol, LDL cholesterol, triglycerides, MDA and gives an effect higher HDL cholesterol.